STRATEGI PENGGUNAAN MEDIA SOSIAL INSTAGRAM DALAM MEMBANGUN BRAND AWARENESS (Studi Kasus Pada Akun Instagram Mazlem.id) - Rizal Nurfaizi; Hasan Basri Tanjung; Muhyani Muhyani (Universitas Pahlawan Tuanku Tambusai, 2022)
In this digital era, social media is a tool used by people who want to build their business. Every product, service, or company needs a place to present or advertise themselves. Mazlem.id is an Indonesian Muslim fashion company that uses social media to advertise its products. Instagram is a social networking platform used by Mazlem.id today. Instagram is a social media channel that Mazlem.id uses to raise awareness. Based on this background, the purpose of this research is to find out how Mazlem.id uses social media to communicate with its target audience and increase brand awareness. Constructivism is the paradigm used in this research, which uses qualitative methods. Descriptive research using case study research methodology is this type of study. In addition to interviewing two Mazlem.id users, the subjects of this research include Mazlem.id employees who work in the company's social media section. By conducting in-depth interviews, collecting information, and making observations, the authors used data collection techniques. The findings of this study indicate that using Instagram social media and creating visual content, promotional campaigns, donation campaigns, and Islamic branding strategies by creating da'wah campaigns, which are based on engagement on social media is a good strategy for using mazlem.id to build brand awareness through the media. online to find out what the behavior of potential consumers who interact on the Mazlem.id Instagram account is like. Keyword: Strategies, Social Media, Brand Awareness.